Mr. Kekerasan Seksual di Kampus: Evaluasi Kebijakan Pemerintah dan Persepsi Masyarakat Melalui Studi Agni Mahasiswa Universitas Gadjah Mada - Waskito Aji, Ginanjar Agung; Fadholi Rofif, Muhammad; Raidar, Usman; Wibisono, Damar; Mahmud, Imam (Institut Manajemen Wiyata Indonesia, 2025)
Sexual violence in the university environment is an increasingly important issue to address, especially in Indonesia, where many victims of cases that are not handled properly and receive little attention so that they do not get justice. The case study of Agni at Universitas Gadjah Mada (UGM) reflects the serious challenges in handling sexual violence. Through a qualitative approach from various sources, such as mass media, journals, and news to analyze the factors that influence the findings, there is a lack of understanding of sexual violence. Added specific details about data sources (n=25 media articles, n=12 peer-reviewed journals, policy documents), sampling strategy, and analysis technique (thematic content analysis). There is also social stigma and victim blaming that prevent victims from reporting. The media has a role in shaping public perception of this issue. This study suggests that there is a need for better education on gender equality and sexual violence, as well as evaluating and improving existing policies to provide effective protection for victims. Explicitly articulated the study's novelty through three dimensions: (1) integrated analysis of institutional policy, media discourse, and victim-centered perspectives, (2) focus on implementation gaps in Indonesian context, (3) contribution to Southeast Asian university literature. With the right steps, it is hoped that the educational environment will become a safe and supportive place for all students, so that they can get a safe place to study without fear of violence.